(Some) refugees welcome: When is differentiating between refugees unlawful discrimination? - Costello, Cathryn; Foster, Michelle (International Journal of Discrimination and the Law, 2022)
Europe’s extraordinary response to those fleeing the Russian invasion of Ukraine in February 2022 has prompted many criticisms of Europe’s treatment of other refugees, and indeed people of colour and members of ethnic minorities fleeing Ukraine. While stark, this differentiated response in not unusual: The global refugee regime treats different refugees differently, as a matter of course. Refugees often encounter racialized migration controls, and systems which privilege some refugees over others. The article seeks to clarify when these practices violate the international legal prohibitions on discrimination on grounds of race and nationality. To do so, it focuses on race discrimination in general international human rights law, clarifying the interaction between general human rights principles and instruments, and the specialist instrument in the field, the International Convention on the Elimination of all Forms of Racial Discrimination. We identify how differences in treatment on grounds of nationality may engage the prohibition on race discrimination both directly (in particular when nationality equates to national origin) or indirectly. Concerning nationality discrimination, the article focuses in particular on the added value of Article 3 of the 1951 Convention on the Status of Refugees, which obliges states to ‘apply the provisions of this Convention to refugees without discrimination as to race, religion or country of origin.’ We examine Article 3 both within the overall scheme of the Refugee Convention and as a source to guide interpretation of international human rights norms.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Article 3; asylum-seekers; discrimination; national origin; nationality; race; Refugee; Refugee Convention